Mixed convective transport in inclined porous open arc-shaped enclosures saturated by nanofluids using a second-order Boussinesq approximation - Sameh E. Ahmed; Z.A.S. Raizah; Ali Chamkha (Case Studies in Thermal Engineering, 2021)
Numerical simulations are performed for the mixed convective transport in an inclined open arc-shaped channel filled by isotropic porous media using nanofluids. The Darcy regime is considered and the non-linear Boussinesq approximation (NBA) is applied for the mixture density. The vorticity-stream function scheme based on the finite volume method in case of the non-orthogonal grids is conducted to solve the dimensionless governing system of equations. The local thermal equilibrium model between the mixture and the porous medium is taken into account and water is considered as a base fluid while the Al2O3 is assumed as nanoparticles. The computations are carried out for various values of the curvature parameter ε ranging from 0.1 to 0.5, the Darcy number Da ranging from 10−2 to 10−5, the Rayleigh number ranging from 104 to 107, the Reynolds number Re ranging from 10 to 5×102, the inclination angle γ ranging from 0 to π2, the nonlinear Boussinesq parameter ξ ranging from 0 to 3 and the nanoparticles volume fraction is varied from 0 % to 4 %. The results reveal that an increase in the nonlinear Boussinesq parameter enhances the average Nusselt number regardless of the values of the inclination angle.